Therapeutic efficacy of neuromuscular electrical stimulation and electromyographic biofeedback on Alzheimer's disease patients with dysphagia. Issue 36 (September 2017) - Tang, Yi; Lin, Xiang; Lin, Xiao-juan; Zheng, Wei; Zheng, Zhi-kai; Lin, Zhao-min; Chen, Jian-hao
Abstract : Abstract: To study the therapeutic effect of neuromuscular electrical stimulation and electromyographic biofeedback (EMG-biofeedback) therapy in improving swallowing function of Alzheimer's disease patients with dysphagia. A series of 103 Alzheimer's disease patients with dysphagia were divided into 2 groups, among which the control group (n = 50) received swallowing function training and the treatment group (n = 53) received neuromuscular electrical stimulation plus EMG-biofeedback therapy. The mini-mental state scale score was performed in all patients along the treatment period. Twelve weeks after the treatment, the swallowing function was assessed by the water swallow test. The nutritional status was evaluated by Mini Nutritional Assessment (MNA) as well as the levels of hemoglobin and serum albumin. The frequency and course of aspiration pneumonia were also recorded. No significant difference on mini-mental state scale score was noted between 2 groups. More improvement of swallowing function, better nutritional status, and less frequency and shorter course of aspiration pneumonia were presented in treatment group when compared with the control group. Neuromuscular electrical stimulation and EMG-biofeedback treatment can improve swallowing function in patients with Alzheimer's disease and significantly reduce the incidence of adverse outcomes. Thus, they should be promoted in clinical practice.